PERANAN NOTARIS DALAM PENGESAHAN ANGGARAN DASAR PERSEROAN TERBATAS MELALUI SISTEM ADMINISTRASI BADAN HUKUM (AHU ONLINE) - I KADEK ADI SURYA; Putu Andhika Kusuma Yadnya; I Dewa Gede Budiarta (VYAVAHARA DUTA, 2023)
Legal Entity Administration System or SABH (formerly known as Sisminbakum) is a type of legal service provided to the business community in the process of ratifying PT legal entities, granting approval for changes to the articles of association of PT, receiving notification of changes to the articles of association of PT and changes to PT data, as well as notification of information others electronically (via computer networks and the internet), organized by the Directorate General of General Legal Administration (Ditjen AHU) at the Ministry of Law and Human Rights of the Republic of Indonesia. Prior to 2000, the process of legalizing a limited liability company was done manually, starting from receiving files which included checking names, payments and making control cards, so it took quite a long time. The enforcement of the SABH began on October 4, 2000 based on the Decree of the Minister of Justice and Human Rights of the Republic of Indonesia number M-01.HT.01.01 of 2000. To establish a company, it must meet the requirements and procedures that have been determined by the Limited Liability Company Law. The establishment of a Limited Liability Company must meet the following requirements: a.) The company is established by two or more persons with a notarial deed drawn up in the Indonesian language, b.) Each company founder is required to subscribe to shares at the time the company is established, c.) The company obtains status of a legal entity on the date of issuance of a ministerial decree concerning the legalization of a legal entity of a company and d.) After the company has obtained the status of a legal entity and the shareholders have become less than two persons, within a period of no later than six months as of the said situation, the shareholder concerned is obliged to transfer part of its shares to other people or the company issues new shares to other people. With the enactment of the Decree of the Minister of Justice and Human Rights of the Republic of Indonesia number M-01.HT.01.01 of 2000 concerning the implementation of the administrative system of legal entities, the process of legalization of legal entities is carried out electronically replacing the old system, namely manual registration of legal entities.